GA Based Feature Recognition of Step File for CAD/CAM Integration - Syafnil, Alfais Admiral (2009)
Feature-based method has been successfully applied in several fields of manufacturing. However, most of the applications use the solid modeling method that cannot meet the requirements of a product design that needs a free-form surface or a complicated surface. This research utilizes the Genetic Algorithm (GA) technique for feature recognition of STEP file. A GA model is proposed for optimizing the coordinates which is used for feature recognition. It is proposed as an input for automatic feature recognition in Computer Aided Design and Manufacturing (CAD/CAM) application. These methods accomplish their task based on recognition of features as GA made up. This technique used standard for exchange of product information (STEP) formats for geometrical data extraction representation to matching the coordinate from STEP file to decide the correct or optimize solution. Genetic operator such as selection, crossover and mutation are performed repeatedly to acquire the optimal sequences of coordinates. Even though the result of this processes are optimal, some coordinates are not placed in the correct position.